A review on membrane fouling control in anaerobic membrane bioreactors by adding performance enhancers. (April 2021) - Sohn, Weonjung; Guo, Wenshan; Ngo, Huu Hao; Deng, Lijuan; Cheng, Dongle; Zhang, Xinbo
Highlights: Addition of fouling reduction enhancers can mitigate membrane fouling in AnMBRs. Activated carbon, biochar, and zeolite can act as an adsorbent in AnMBRs. Calcium, iron and polyaluminum chloride can act as a flocculant and a coagulant. Waste yeast and beads could act as a co-substrate and biocarriers, respectively. Overdosing or large particle size of enhancers might aggravate fouling. Abstract: Anaerobic membrane bioreactors (AnMBRs), the combination of anaerobic digestion and membrane technology, have gained increasing popularity due to their remarkable advantages over aerobic membrane bioreactors, such as biogas production and potential energy use. However, membrane fouling remains a challenging issue that deteriorates the performance of membrane and shortens its lifespan. Pretreatment of feed wastewater by adding fouling reduction enhancers, such as adsorbents and flocculants, into anaerobic membrane bioreactor can effectively mitigate membrane fouling by altering the feed properties. Activated carbon, such as powdered activated carbon (PAC) and granular activated carbon (GAC), has been widely applied as an adsorbent to aerobic and anaerobic membrane bioreactors for membrane fouling control. Organic enhancers such as biochar and waste yeast, and inorganic enhancers like polyaluminum chloride and zeolite have also been applied to AnMBRs promoting flocculation and coagulation. Thus, this review discusses the impacts of different fouling reduction enhancers under anaerobic conditions as well as AnMBR system. In addition, the mechanisms of the enhancers mitigating the membrane fouling are also summarized for better understanding of the effects of the enhancers in AnMBRs.